Effect of hypoxia on the post-hatching growth of the body of the fry and the caudal fin of the Atlantic Salmon (Salmo salar) - Rojas, Mariana; Salvatierra, Renato; Smok, Carolina; Sandoval, Cristian; Souza-Mello, Vanessa; del Sol, Mariano (Frontiers in Marine Science, 2024)
Hypoxia is a recurring problem in the fish farming industry. Currently, it is known that the exposure of fish and fry to a hypoxic environment induces important changes in their metabolism, compromising not only their development but also their reproduction and mortality rates. Our hypothesis is that hypoxia constitutes one of the etiological factors causing deformation of the body and caudal fin in this species, as well as affecting its growth. We analyzed two hundred forty Salmo salar salmon fry, differentially cultured at 100 % saturation (normoxia condition) and 60 % (hypoxia condition) for 2, 4, 6, and 8 days, including a group under continuous hypoxia. We performed diaphanization and Alcian blue staining, along with standard histological techniques. The polyclonal anti-HIF-1α antibody was used as a marker of hypoxia in Salmo salar, and hypoxia in these fish was associated with the immunopositivity of this antibody. The results indicate that there is an association between exposure to hypoxia and the deformation of the body and fin, as well as an agreement between hypoxia and the total length of the fry and fin. Several months after the event occurred, we were able to find and describe angiogenesis, blood vessel disorganization, and vasodilation histologically. Finally, hypoxic cells in the fry (HIF-1α) could be recognized and confirmed as hypoxia sensors. All of this indicates that hypoxia not only affects the fry during the development phase of the event, but that its results can be evident much later and affect the fry throughout their entire ontogeny.